2006
DOI: 10.1016/j.exppara.2005.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcus multilocularis: Developmental stage-specific expression of Antigen B 8-kDa-subunits

Abstract: Antigen B (AgB) initially found in hydatid cyst fluid of Echinococcus granulosus is a polymeric lipoprotein of 160 kDa, and is an aggregate of several different but homologous small proteins with approximately 8 kDa. Four genes encoding these 8-kDa-subunits have been identified from E. granulosus. In this study we isolated five genes encoding 8-kDa-subunits of AgB from Echinococcus multilocularis. Sequence comparison of isolated cDNA clones demonstrated that one of these five clones was completely identical to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
46
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 23 publications
8
46
0
Order By: Relevance
“…They reported that the observed sequence heterogeneity of the AgB genes in different geographic origin could reflect the occurrence of distinct clonal populations of which differed in the use of their final and intermediate hosts and morphological, biochemical, and genetic characteristics. Their finding is supported by Mamuti et al [6] who concluded that the genetic variability in different host and/or different level of host immune responses against AgB may be relevant factors in the variability that is observed in the immunogenecity of AgB among different CE patients. In addition, Rosenzvit et al [7] reported that analyzing the variation of AgB-coding genes may provide a specific correlation of strain genetic diversity with AgB functional and practical significance.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…They reported that the observed sequence heterogeneity of the AgB genes in different geographic origin could reflect the occurrence of distinct clonal populations of which differed in the use of their final and intermediate hosts and morphological, biochemical, and genetic characteristics. Their finding is supported by Mamuti et al [6] who concluded that the genetic variability in different host and/or different level of host immune responses against AgB may be relevant factors in the variability that is observed in the immunogenecity of AgB among different CE patients. In addition, Rosenzvit et al [7] reported that analyzing the variation of AgB-coding genes may provide a specific correlation of strain genetic diversity with AgB functional and practical significance.…”
Section: Discussionsupporting
confidence: 75%
“…It is one of the most abundant parasite antigens in HCF and commonly used in immunodiagnosis of CE [5]. It is involved in the evasion of the immune response of the host due to its ability to inhibit elastase activity and neutrophils recruitment and to elicit an immunopathology-associated T-helper 2 (Th2) cell response, predominantly in patients with progressive CE [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomic and genomic analyses demonstrated that the same gene encoded these proteins. A previous report indicated that this gene was actively transcribed during the metacestode stage (28). We also observed expression of the mRNA transcript of the EmAgB3 gene by real-time RT-PCR (unpublished observation).…”
Section: Discussionmentioning
confidence: 49%
“…Its role in parasite biology has not yet been completely elucidated. Antigen B expression is associated with immature stages in E. multilocularis (Carmena et al 2006;Mamuti et al 2006). Its main function seems to be the inhibition of elastase activity, though it seems to have no effect on trypsin or chemotrypsine activity (Shepherd et al 1991).…”
Section: Discussionmentioning
confidence: 99%